2000
DOI: 10.1029/2000jb900233
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic response to strike‐ and dip‐slip faulting in a half‐space

Abstract: Abstract. Field observations have shown strong coupling between earthquake-induced stress-strain fields and subsurface hydrodynamics, reflected by water level change in wells and stream flow fluctuations. Various models have been used in an attempt to interpret the coseismic fluctuations in groundwater level, predict water table rise in the event of an earthquake, and explain stream flow variations. However, a general model integrating earthquake-induced stress-strain fields, coseismic pore pressure generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 36 publications
3
66
0
1
Order By: Relevance
“…We assumed that the observed streamflow variations are the hydrological response to coseismic strain changes (MuirWood and King, 1993). Several studies demonstrate that the polarities of calculated deformation are in agreement with those of the observed hydrological effects so that extensional strain produces a discharge fall and compressive strain a discharge rise, especially in the near field (Grecksch et al, 1999;Ge and Stover, 2000;Lee et al, 2002;Montgomery and Manga, 2003;Caporali et al, 2005).…”
Section: Hydrological Data and Models Of Coseismic Strainsupporting
confidence: 54%
See 1 more Smart Citation
“…We assumed that the observed streamflow variations are the hydrological response to coseismic strain changes (MuirWood and King, 1993). Several studies demonstrate that the polarities of calculated deformation are in agreement with those of the observed hydrological effects so that extensional strain produces a discharge fall and compressive strain a discharge rise, especially in the near field (Grecksch et al, 1999;Ge and Stover, 2000;Lee et al, 2002;Montgomery and Manga, 2003;Caporali et al, 2005).…”
Section: Hydrological Data and Models Of Coseismic Strainsupporting
confidence: 54%
“…In particular, MuirWood and King (1993) found that hydrological changes would accompany major normal fault, showing increase in streamflow and spring rise; reverse faults, on the contrary, would show negligible or undetectable effects, whilst strike slip and oblique faults would generate a combination of responses. Recently, the spatial pattern of water level changes has been compared with simulated coseismic strain changes (Grecksch et al, 1999;Ge and Stover, 2000;Lee et al, 2002;Montgomery and Manga, 2003;Caporali et al, 2005). The area interested by contractional volumetric strain seems to be in good agreement with the water level rise and water excess in streamflows.…”
Section: Hydrological Changesmentioning
confidence: 78%
“…Such changes can include step-changes in water level, water-level oscillations, and sustained change in water level [8][9][10][11]. Usually, a step-change in water level is considered to be caused by static stress release as fault slips [12][13][14][15]. Seismic waves can also lead to step-changes [10] and oscillations [2,[16][17][18] in groundwater level.…”
mentioning
confidence: 99%
“…Generally, larger changes, up to 11.09 m, were found in wells closer to the fault. These co-seismic changes were likely caused by coseismic strain induced by fault displacement (Wakita 1975;Roeloffs 1988;Grecksch et al 1999;Ge and Stover 2000;Chia et al 2001Chia et al , 2008b. The distribution of the sustained changes in the footwall revealed that crustal extension dominated near the Chelungpu fault during the earthquake, while compression prevailed away from the fault.…”
Section: Chi-chi Earthquake and Co-seismicmentioning
confidence: 99%